The impact of first- and second-eye cataract surgery on motor vehicle crashes and associated costs. - Meuleners, L.; Brameld, Kate; Fraser, M.; Chow, Kyle (Oxford University Press, 2018)
Objective: to evaluate the association between first- and second-eye cataract surgery and motor vehicle crashes for older drivers and the associated costs to the community. Design: retrospective population-based cohort study. Subjects: a total of 2,849 drivers aged 60 years and older who had undergone both first- and second-eye cataract surgery were involved in 3,113 motor vehicle crashes as drivers during the study period. Methods: de-identified data were obtained using the Western Australian Data Linkage System from 1 January 2003 to 31 December 2015. Poisson regression analysis based on Generalised Estimating Equations was undertaken to compare the frequency of crashes in the year before first eye cataract surgery, between first and second eye surgery and 1 year after second eye surgery. Results: first eye cataract surgery was associated with a significant 61% reduction in crash frequency (P < 0.001) and second eye surgery was associated with a significant 23% reduction in crashes (P < 0.001), compared to the year before first eye cataract surgery after accounting for age, gender, marital status, accessibility, socio-economic status, driving exposure and comorbidities. The estimated cost savings from the reduction in crashes in the year after second eye cataract surgery compared to the year before first eye cataract surgery was $14.9 million. Conclusions: first- and second-eye cataract surgery were associated with a significant reduction in motor vehicle crashes, with first eye surgery having the greatest impact. These results provide encouragement for the timely provision of first- and second-eye cataract surgery for older drivers.